The Effect of Sales Promotion, Electronic Word of Mouth and Online Customer Experience on Repurchase Intention (Case: Shopee Marketplace Users in Padang, Indonesia) - Setiani, Novelia Ghani; Syafrizal, Syafrizal; Triani, Laura Amelia (Management Institute Faculty of Economics Universitas Andalas, 2024)
The increasingly rapid development of technology and accompanied by consumer behavior tends to buy and sell online to meet their daily needs. One of which is through an online marketplace. This research aimed to observe the effect of sales promotion, electronic word of mouth and online customer experience on repurchase intention. This research used a hypothesis test method with a research sample of 230 Shopee’s customer in Padang taken by non-probability sampling technique. The research data processing was carried out to see the influence between the independent and the dependent variable with the SmartPLS version 3.3.3 program. The results of this research indicated that sales promotion had a positive but not significant effect on repurchase intention. Meanwhile, electronic word of mouth and online customer experience had a positive and significant effect on repurchase intention.